Groundwater response to changin climate - Taniguchi, Makoto | Holman, Ian P (CRC PRES / New York, 2010)
Groundwater systems are vital to both society and the environment, supporting food production and many other ecosystem services. Sustainable management of this vital resource for future generations requires a sound understanding of how groundwater might respond to the inevitable changes in future climate. In this volume, recent developments within